Prevalence of HPV Genotypes in South Europe: Comparisons between an Italian and a Turkish Unvaccinated Population. (19th May 2019) - Schettino, Maria Teresa; De Franciscis, Pasquale; Schiattarella, Antonio; La Manna, Viviana; Della Gala, Alessandra; Caprio, Francesca; Tammaro, Carolina; Ammaturo, Franco Pietro; Guler, Tolga; Yenigün, Ezgi Hanci
Abstract : The human papilloma virus (HPV) is a DNA virus associated with benign and malignant lesions of skin and mucous membranes and is the most common sexually transmitted viral infection worldwide. We investigated the prevalence of HPV infection and associated risk factors in Italian and Turkish women population attending the gynecology outpatients clinic in Naples (Italy) and Pamukkale (Turkey). Women were enrolled from the Department of Obstetrics and Gynecology of the University of Campania "Luigi Vanvitelli" in Naples (Italy) and of "Pamukkale University" in Denizli (Turkey) between January 2014 and June 2015. A questionnaire that included sociodemographic and sexual behavior characteristics, questions about HPV awareness, vaccine status, and reasons for not wanting to get vaccinated, and HPV-related knowledge was completed for each participant, and cervical cytology samples were collected. The prevalence of HPV infection was higher in the Italian group (52.6% vs 32.6%, p < 0.001 ), while the distribution of genotypes is similar (p = 0.325 ). Moreover, the differences in cytological alterations in these patients are significant (p < 0.001 ). The analysis showed a higher prevalence of sexual behavioral characteristics (p < 0.001 ) and better attention to the execution of the screening test in the Italian population (p < 0.001 ). Italian women showed more knowledge and propensity to vaccination compared to Turkish women (p < 0.001 ). Our data highlighted three relevant aspects: the different prevalence of cytological abnormalities, the different distribution of risk factors and, above all, the different attitude of women towards the primary prevention of cervical cancer between an Italian and a Turkish population group.